Editorial Board - Journal, HEROS (Helsinki Romanian Studies Journal, 2024)
EDITORIAL BOARD Editor-in-Chief Emilia IVANCU – Helsinki University, Finland Editor, Section Editor Tomasz KLIMKOWSKI – Adam Mickiewicz University of Poznań, Poland Layout Editor, Proofreader Oana TOPALĂ – Fédération Wallonie-Bruxelles, Belgium ADVISORY BOARD Ioana Bican – Babes-Bolyai University, Cluj-Napoca, Romania Cristina Bogdan – University of Bucharest, Romania Radu Bogdan – Tulane University, New Orleans, USA Roxana Ciolăneanu – University of Lisbon, Portugal Silvio Cruschina – Helsinki University, Finland Daiana Cuibus – Babes-Bolyai University/Romanian Language Institute, Romania Baudouin Decharneux – L’Université Libre de Bruxelles (ULB), Belgium Iulia Dondorici – Freie Universität Berlin, Germany Cécile Folschweiller - INALCO, Paris, France Gabriela Gavril – Al. I. Cuza University of Iași, Romania Jukka Havu – University of Tampere, Finland Kazimierz Jurczak – Jagiellonian University, Krakow, Poland Thede Kahl – Friedrich Schiller University, Jena, Germany Martin Maiden – University of Oxford, UK Roberto Merlo – University of Turin, Italy Matti Miestamo – Helsinki University, Finland Oana Murăruș – University of Bucharest, Romania Paul Nanu - University of Alba Iulia, Romania Nicoleta Neșu – Sapienza University of Rome, Italy Florin Oprescu - Universität Wien, Austria Jana Palenikova – Comenius University Bratislava, Slovakia Cristian Preda – University of Bucharest, Romania Teodora Șerban-Oprescu – Bucharest University of Economic Studies Fernando Sánchez-Miret – The University of Salamanca, Spain Gabriel Sandu – Helsinki University, Finland Ingmar Söhrman – University of Gothenburg, Sweden Annemarie Sorescu-Marinković – Institute for Balkan Studies, Belgrade Alice Toma – L’Université Libre de Bruxelles (ULB), Belgium